Modified recycled aggregate carbon sequestration bare concrete and preparation method thereof

Through the modification of carbon separator, the existing modified carbon separator recycled concrete process is solved, and the efficient modification of recycled aggregates and the improvement of concrete performance is achieved, which meets the environmentally friendly and green low-carbon requirements.

CN119613054AActive Publication Date: 2025-03-14GUIZHOU CSCEC SHUANGYUAN BUILDING MATERIALS CO LTD +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411993006.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-14
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing modified carbon-solid recycled concrete process is complex, which increases the cost of recycled aggregate modification, making it difficult to achieve large-scale application.

Method used

The regenerated aggregate is modified by using carbon sediment agent, and a porous structure is formed by stirring nano-level vapor-phase silica and deionized water. Combining sodium silicate and sodium hydroxide, an efficient carbon sediment agent is formed, reducing the water absorption rate of the regenerated aggregate and improving its compactness.

Benefits of technology

The recycled aggregate modification process is simplified, the modification cost is reduced, the performance and durability of concrete is improved, the cement consumption and carbon emissions are reduced, and the preparation of environmentally friendly and green low-carbon recycled concrete is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses modified recycled aggregate carbon-sequestration bare concrete and a preparation method thereof, belongs to the field of modified carbon-sequestration recycled concrete, and aims to solve the problem that multiple processes or equipment can be added for modification treatment of recycled aggregate in different ways regardless of pre-wetting treatment or carbonization treatment, so that the service life of the recycled aggregate is greatly prolonged. According to the present invention, the recycled aggregate modification material comprises the following components by mass: 140-180 parts of phosphorus slag, 190-230 parts of industrial solid waste composite powder, 30-40 parts of ordinary Portland cement, 710-760 parts of recycled sand, 890-940 parts of recycled gravel, 140-150 parts of water, 7-10 parts of an additive, 134-150 parts of a carbon fixation agent, and 3-5 parts of a GU release agent. The alkali-activated industrial solid waste composite powder is recycled, carbon emission in the concrete production process is reduced, and meanwhile, the alkali-activated industrial solid waste composite powder is matched with a special carbon fixing agent for use, so that the primary defects of recycled aggregate are effectively overcome. The simple and convenient modification pretreatment process of the recycled aggregate is realized, and the workability, the strength, the apparent quality and the carbon sequestration rate of the recycled aggregate bare concrete are greatly optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of modified carbon-fixing regenerated concrete, and in particular relates to a modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof. Background Art

[0002] With the development of the concept of recycling renewable resources, these construction wastes can now be generally used as aggregates for some conventional concrete after being crushed. However, the recycled aggregates themselves have disadvantages such as high water absorption and large crushing value. If we want to further increase the proportion of recycled aggregates in concrete, we often need to modify the recycled aggregates before using them. In the current field of modified carbon-fixed recycled concrete, there are many different ways to modify recycled aggregates, but whether it is pre-wetting treatment or carbonization treatment, it will add multiple processes or equipment, which will greatly increase the cost of recycled aggregate modification. How to simplify the modification process of recycled aggregates, reduce the modification cost of recycled aggregates, and realize the large-scale application of recycled aggregates still needs further improvement. Summary of the invention

[0003] The present invention provides a modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof, which greatly simplifies the modification process of recycled aggregates, effectively improves the performance of recycled aggregates by modifying the recycled aggregates with a carbon-fixing agent, and quickly absorbs carbon dioxide by utilizing the high adsorption of carbon dioxide by the carbon-fixing agent. At the same time, efficient carbon fixation and internal curing are achieved by utilizing the characteristics of the recycled aggregates, thereby converting the defects of the recycled aggregates into advantages, further improving the performance of concrete, and based on the proportion of large-volume mineral admixtures, reducing the amount of cement used, reducing production carbon emissions, and realizing a modified carbon-fixing recycled aggregate plain concrete preparation technology that is environmentally friendly, green, and low-carbon.

[0004] The technical solution according to this application is:

[0005] Preferably, the modified carbon-fixing recycled aggregate plain concrete has the following raw material components in the following mass ratios: 140-180 parts of phosphorus slag: 190-230 parts of industrial solid waste composite powder: 30-40 parts of ordinary Portland cement: 710-760 parts of regenerated sand: 890-940 parts of regenerated gravel: 140-150 parts of water: 7-10 parts of admixture: 134-150 parts of carbon-fixing agent: 3-5 parts of GU release agent.

[0006] Preferably, the mass ratio of the components in the carbon fixer is: fumed silica: 25-33 parts: deionized water: 225-300 parts: sodium silicate: 3-5 parts: sodium hydroxide: 1-3 parts.

[0007] Preferably, the particle size of the fumed silica is 10-20 nm, and the purity reaches 99.9%.

[0008] Preferably, the sodium silicate is white powder with a purity of 98%.

[0009] Preferably, the sodium hydroxide is in the form of flaky crystals with a purity of 95%.

[0010] Preferably, the ordinary Portland cement is one of P·O425 cement, P·O425R cement, P·O525 cement, and P·O525 cement.

[0011] Preferably, the phosphorus slag powder is white powder with an activity of 93%.

[0012] Preferably, the industrial solid waste composite powder is one or more of fly ash, mineral powder, steel slag, water-quenched slag, metakaolin, electrolytic manganese slag, ferronickel slag, and copper slag.

[0013] Preferably, the regenerated sand is collected during the crushing of construction solid waste, has a fineness modulus of 2.9, a base powder content of 7%, a water absorption rate of 8.1%, and a crushing value of 21.3%.

[0014] Preferably, the regenerated gravel is 5-25 mm gravel, with a crushing value of 13.4% and a water absorption rate of 6.4%;

[0015] Preferably, the GU release agent is a silane coupling agent or a polyvinyl alcohol-acrylate copolymer.

[0016] Preferably, the carbon fixer modified recycled aggregate process is as follows:

[0017] Step 1: Weigh the raw materials in the carbon fixer according to the mass ratio, put the fumed silica into the planetary mixer and start stirring at a speed of 120r / min, and use a catheter to introduce deionized water into the mixer at a speed of 500ml / min. During the process, the mixer keeps running. After the deionized water is introduced, the speed is increased to 600r / min, and stirring is maintained for 10 to 15 minutes to finally obtain a mixture of powdered fumed silica and deionized water;

[0018] Step 2: Add sodium silicate powder and sodium hydroxide into the mixture obtained in step 1, and stir the mixture at a speed of 120 r / min. During the stirring process, water is added to rinse the surface of the stirring pot to reduce the temperature in the stirring pot. Stirring is stopped after 5 to 8 minutes, and the carbon fixer is prepared.

[0019] Step 3: Pour the weighed regenerated sand and regenerated gravel into a container, and then pour the prepared carbon fixer into the same container, and remix the regenerated sand and regenerated gravel every 30 minutes. After 8 hours, the modified regenerated sand and modified regenerated gravel are obtained.

[0020] The preparation principle of the carbon fixer is as follows: the performance of nanometer-level fumed silica is stable, and it has a large number of bonded silanol groups. At the same time, due to the presence of silanol groups, it has obvious shear-thinning characteristics. When stirred at a speed of 60r / min, the fumed silica initially breaks up, wraps up, and evenly spreads the deionized water everywhere. When the speed is increased to 600r / min, the fumed silica continuously breaks up the deionized water into small water droplets, and under the action of silanol groups, the fumed silica continuously forms network agglomerates to wrap up the small water droplets. Finally, after forming a nearly powdery state, sodium silicate and sodium hydroxide are added. Sodium silicate and sodium hydroxide are rapidly dispersed and dissolved into the small water droplets during the stirring process, and because of sodium silicate and sodium hydroxide, the surface tension of the small water droplets increases rapidly. At this time, the fumed silica agglomerates tightly wrap the small water droplets of the composite solution of sodium silicate and sodium hydroxide, the overall viscosity increases, and the shear-thinning performance weakens. The nearly powdery substance obtained at this time is the carbon fixer.

[0021] Preferably, the preparation process of the modified recycled aggregate carbon-fixing plain concrete and the preparation method thereof is as follows:

[0022] Step 1: Weigh phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand, modified regenerated gravel, water, admixture, carbon fixer, GU release agent, etc. according to the mass ratio of each component;

[0023] Step 2: Add the phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand and modified regenerated gravel weighed in step 1 according to the mass ratio of each component into a mixer and stir for 10 to 15 seconds to mix the powders and aggregates evenly;

[0024] Step 3: Add the water and admixture weighed in the mass ratio of each component in step 1 to the mixture stirred evenly in step 2, and continue stirring in the mixer for 240-300 seconds. At this time, apply GU release agent evenly on the inner wall of the formwork, and pour it into the mold after the concrete mixing is completed.

[0025] The beneficial effects of the present invention are:

[0026] (1) In the present invention, the amount of ordinary silicate cement used is very small, and industrial solid waste raw materials are basically used. In addition to phosphorus slag powder, the main components of the industrial solid waste composite powder are CaO, SiO2, Al2O3 and other inactive metal oxides and metals with potential activity. As the cement hydration process proceeds, hydrated calcium silicate gel and calcium hydroxide appear in the concrete. After sufficient stirring, the carbon fixer added together with the modified recycled aggregate is also dispersed into the concrete. The sodium silicate and sodium hydroxide in the carbon fixer and the calcium hydroxide product in the slurry provide an alkaline environment for the industrial solid waste composite powder. The potential active oxides in the industrial solid waste composite powder quickly produce a hydration reaction to generate a completely different product, hydrated calcium aluminosilico gel, and quickly form a strong structure. In the entire concrete production and preparation process, only a small part of cement is used, and the remaining raw materials are all industrial solid waste or construction waste, which effectively reduces pollution and carbon emissions in the production process.

[0027] (2) In the process of modifying the recycled aggregate, firstly, the micro-nano size of the carbon fixer can easily flow into the gaps in the mortar layer on the surface of the recycled aggregate. 95% of the carbon fixers left in the gaps in the mortar layer are water molecules, which basically realizes the "pre-wetting" treatment of the recycled aggregate, thereby quickly and effectively reducing the water absorption rate of the recycled aggregate; secondly, after the concrete is formed, it will continue to be eroded by carbon dioxide in the air. Based on the micro-nano porous structure of the carbon fixer, this structure has a strong adsorption capacity for carbon dioxide. After the carbon dioxide enters the concrete, it will easily enter the gaps in the recycled aggregate and be captured and adsorbed by the carbon fixer. This part of the carbon dioxide will react with the surface of the recycled aggregate. Calcium hydroxide in the surface mortar layer reacts to form calcium carbonate, which will fill the pores between the recycled aggregate mortar layers, thereby further improving the density of the recycled aggregate and reducing the crushing value of the recycled aggregate; thirdly, as the strength of concrete develops, microcracks will inevitably form inside the concrete due to shrinkage, and carbon dioxide in the air will preferentially enter the concrete along the microcracks. In this process, carbon dioxide will be directly absorbed by the carbon fixer in the microcracks and react directly with sodium hydroxide to form sodium carbonate, and sodium carbonate crystals will subsequently precipitate to fill the gaps, so that the concrete can continuously absorb carbon dioxide and continuously improve its strength and durability throughout its service life.

[0028] (3) In the present invention, the GU release agent is applied on the formwork. After the concrete is poured into the formwork, one end of the silane coupling agent is coupled to the polyvinyl alcohol-acrylate copolymer, and the other end is adsorbed on the concrete surface. The hydrophobic end of the polyvinyl alcohol-acrylate will face away from the concrete surface. When the concrete hardens, the polyvinyl alcohol-acrylate forms a smooth hydrophobic layer on the concrete surface, thereby improving the surface quality of the concrete. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below through specific implementation examples, which are intended to explain the present invention rather than to limit it.

[0030] Embodiment 1:

[0031] S1: 25 parts of fumed silica, 225 parts of deionized water, 3 parts of sodium silicate, and 1 part of sodium hydroxide are weighed by mass.

[0032] S2: Put the weighed fumed silica in S1 into a mixer, put the fumed silica into the planetary mixer and start stirring at a speed of 120 r / min, and use a catheter to introduce deionized water into the mixer at a speed of 500 ml / min. During the process, the mixer keeps running. After the deionized water is introduced, the speed is increased to 600 r / min, and stirring is maintained for 10 minutes to obtain a mixture of powdered sugar fumed silica and deionized water;

[0033] S3: Sodium silicate powder and sodium hydroxide are added to the mixture obtained in S2, and the agitator is stirred at a speed of 120r / min. During the stirring process, water is added to rinse the surface of the stirring pot to reduce the temperature in the stirring pot. The stirring is stopped after 5 minutes, and the carbon fixer is prepared.

[0034] S4: Pour the weighed regenerated sand and regenerated gravel into a container, and then pour the prepared carbon fixer into the same container, and remix the regenerated sand and regenerated gravel every 30 minutes. After 8 hours, the modified regenerated sand and modified regenerated gravel are obtained.

[0035] S5: Each raw material component is weighed by mass, including 140 parts of phosphorus slag, 190 parts of industrial solid waste composite powder, 30 parts of ordinary Portland cement, 710 parts of regenerated sand, 890 parts of regenerated gravel, 140 parts of water, 7 parts of admixture, 134 parts of carbon fixer, and 3 parts of GU release agent.

[0036] S6: Add the phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand and modified regenerated gravel weighed in S5 according to the mass ratio of each component into a mixer and stir for 10 seconds to mix the powders and aggregates evenly;

[0037] S7: Add the water and admixture weighed in the mass ratio of each component in S1 to the mixture stirred evenly in S6, and continue stirring in the mixer for 240 seconds. At this time, apply GU release agent evenly on the inner wall of the formwork, and pour it into the mold after the concrete mixing is completed.

[0038] Embodiment 2:

[0039] S1: 33 parts of fumed silica, 300 parts of deionized water, 5 parts of sodium silicate, and 3 parts of sodium hydroxide are weighed according to the mass of each component;

[0040] S2: Put the weighed fumed silica in S1 into a mixer, put the fumed silica into the planetary mixer and start stirring at a speed of 120 r / min, and use a catheter to introduce deionized water into the mixer at a speed of 500 ml / min. During the process, the mixer keeps running. After the deionized water is introduced, the speed is increased to 600 r / min, and stirring is maintained for 15 minutes to obtain a mixture of powdered sugar fumed silica and deionized water;

[0041] S3: Sodium silicate powder and sodium hydroxide are added to the mixture obtained in S2, and the agitator is stirred at a speed of 120r / min. During the stirring process, water is added to rinse the surface of the stirring pot to reduce the temperature in the stirring pot. The stirring is stopped after 8 minutes, and the carbon fixer is prepared.

[0042] S4: Pour the weighed regenerated sand and regenerated gravel into a container, and then pour the prepared carbon fixer into the same container, and remix the regenerated sand and regenerated gravel every 30 minutes. After 8 hours, the modified regenerated sand and modified regenerated gravel are obtained.

[0043] S5: The raw material components are weighed by mass, including 180 parts of phosphorus slag, 230 parts of industrial solid waste composite powder, 40 parts of ordinary Portland cement, 760 parts of regenerated sand, 940 parts of regenerated gravel, 150 parts of water, 10 parts of admixture, 150 parts of carbon fixer, and 5 parts of GU release agent.

[0044] S6: Add the phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand and modified regenerated gravel weighed in S5 according to the mass ratio of each component into a mixer and stir for 15 seconds to mix the powders and aggregates evenly;

[0045] S7: Add the water and admixture weighed in the mass ratio of each component in S1 to the mixture stirred evenly in S6, and continue stirring in the mixer for 300 seconds. At this time, apply GU release agent evenly on the inner wall of the formwork. After the concrete mixing is completed, pour it into the mold for molding.

[0046] Embodiment 3:

[0047] S1: 29 parts of fumed silica, 263 parts of deionized water, 4 parts of sodium silicate, and 2 parts of sodium hydroxide are weighed by mass.

[0048] S2: Put the weighed fumed silica in S1 into a mixer, put the fumed silica into the planetary mixer and start stirring at a speed of 120 r / min, and use a catheter to introduce deionized water into the mixer at a speed of 500 ml / min. During the process, the mixer keeps running. After the deionized water is introduced, the speed is increased to 600 r / min, and stirring is maintained for 12.5 minutes to obtain a mixture of powdered fumed silica and deionized water;

[0049] S3: Sodium silicate powder and sodium hydroxide are added to the mixture obtained in S2, and the agitator is stirred at a speed of 120r / min. During the stirring process, water is added to rinse the surface of the stirring pot to reduce the temperature in the stirring pot. The stirring is stopped after 6.5 minutes, and the carbon fixer is prepared.

[0050] S4: Pour the weighed regenerated sand and regenerated gravel into a container, and then pour the prepared carbon fixer into the same container, and remix the regenerated sand and regenerated gravel every 30 minutes. After 8 hours, the modified regenerated sand and modified regenerated gravel are obtained.

[0051] S5: Each raw material component is weighed by mass, including 160 parts of phosphorus slag, 210 parts of industrial solid waste composite powder, 35 parts of ordinary Portland cement, 735 parts of regenerated sand, 925 parts of regenerated gravel, 145 parts of water, 8 parts of admixture, 142 parts of carbon fixer, and 4 parts of GU release agent.

[0052] S6: Add the phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand and modified regenerated gravel weighed in S5 according to the mass ratio of each component into a mixer and stir for 12 seconds to mix the powders and aggregates evenly;

[0053] S7: Add the water and admixture weighed in the mass ratio of each component in S1 to the evenly stirred mixture in S6, and continue stirring in the mixer for 270 seconds. At this time, apply GU release agent evenly on the inner wall of the formwork, and pour it into the mold after the concrete mixing is completed.

[0054] Comparative Example 1:

[0055] The difference between this comparative example and Example 3 is that no carbon fixer is added, and the recycled aggregate is directly used to prepare concrete;

[0056] Comparative Example 2:

[0057] The difference between this comparative example and Example 3 is that in step S4, no carbon fixer is used to modify the recycled aggregate; the carbon fixer is directly added to the concrete in step S5;

[0058] Comparative Example 3:

[0059] The difference between this comparative example and Example 3 is that in step S7, the template is not coated with a GU release agent;

[0060] Comparative Example 4:

[0061] The difference between this comparative example and Example 3 is that in step S6, the carbon fixer in this patent is not added, and the recycled aggregate is pre-wetted and then drained for trial mixing.

[0062] Performance test: The test results of various properties of a modified carbon-fixing recycled aggregate plain concrete prepared in Examples 1-3 and Comparative Examples 1-4 were as follows:

[0063] Table 1 Concrete performance test results

[0064]

[0065] Data analysis: It can be seen from Examples 1 to 3 that a modified recycled aggregate carbon-fixing plain concrete prepared by the present invention and its preparation method cover concretes of multiple different strength grades. When the variation range of each raw material is within the design range, the concrete can always maintain good workability and compressive strength, and has good apparent quality. It can be clearly seen that the bone carbon rate of the modified carbon-fixing recycled aggregate plain concrete increases with the increase of the concrete strength grade. It can be learned from Comparative Examples 1 to 4 that no matter how the process conditions change, or when the formula is adjusted beyond the range, the various test data of Example 3 are all higher than the comparative example except that the workability is lower than that of the directly pre-wetted recycled aggregate. In addition, the present invention uses phosphorus slag and industrial solid waste composite powder as raw materials, and realizes the recycling of bulk industrial solid waste by recycling and utilizing them, reduces the amount of cement added, and reduces carbon emissions in the concrete production process, meeting the green and low-carbon environmental protection requirements.

[0066] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof, characterized in that: The mass ratio of each raw material component is: 140-180 parts of phosphorus slag: 190-230 parts of industrial solid waste composite powder: 30-40 parts of ordinary Portland cement: 710-760 parts of regenerated sand: 890-940 parts of regenerated crushed stone: 140-150 parts of water: 7-10 parts of admixture: 134-150 parts of carbon fixer: 3-5 parts of GU release agent.

2. According to claim 1, it is characterized in that: The mass ratio of the components in the carbon fixer is: 25-33 parts of fumed silicon dioxide: 225-300 parts of deionized water: 3-5 parts of sodium silicate: 1-3 parts of sodium hydroxide.

3. The carbon fixer according to claim 2, characterized in that: The particle size of the fumed silicon dioxide is 10-20 nm, and the purity reaches 99.9%.

4. A modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof according to claim 1, characterized in that: The ordinary Portland cement is one of P·O425 cement, P·O425R cement, P·O525 cement and P·O525 cement.

5. A modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof according to claim 1, characterized in that: The industrial solid waste composite powder is one or more of fly ash, mineral powder, steel slag, water-quenched slag, metakaolin, electrolytic manganese slag, ferronickel slag, and copper slag.

6. A modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof according to claim 1, characterized in that: The regenerated sand is collected during the crushing of construction solid waste, with a fineness modulus of 2.9, a bottom powder content of 7%, a water absorption rate of 8.1%, and a crushing value of 21.3%. The regenerated crushed stone is 5-25 mm crushed stone, with a crushing value of 13.4% and a water absorption rate of 6.4%.

7. The modified recycled aggregate carbon-fixing plain concrete and preparation method thereof according to claim 1, characterized in that: The GU release agent is a silane coupling agent and a polyvinyl alcohol-acrylate copolymer.

8. A modified recycled aggregate carbon-fixing plain concrete and a preparation method thereof according to claim 1, characterized in that: The carbon fixer modified recycled aggregate process is as follows: Step 1: Weigh the raw materials in the carbon fixer according to the mass ratio, put the fumed silica into the planetary mixer and start stirring at a speed of 120r / min, and use a catheter to introduce deionized water into the mixer at a speed of 500ml / min. During the process, the mixer keeps running. After the deionized water is introduced, the speed is increased to 600r / min, and stirring is maintained for 10 to 15 minutes to finally obtain a mixture of powdered fumed silica and deionized water; Step 2: adding sodium silicate powder and sodium hydroxide to the mixture obtained in step 1, stirring at a speed of 120 r / min, and during the stirring process, washing the surface of the stirring pot with water to reduce the temperature in the stirring pot, and stopping stirring after 5 to 8 minutes, at which time the carbon fixer is prepared; Step 3: Pour the weighed regenerated sand and regenerated gravel into a container, and then pour the prepared carbon fixer into the same container, and remix the regenerated sand and regenerated gravel every 30 minutes. After 8 hours, the modified regenerated sand and modified regenerated gravel are obtained.

9. The modified recycled aggregate carbon-fixing plain concrete and preparation method thereof according to claim 1, characterized in that: The preparation process of the modified recycled aggregate carbon-fixing plain concrete and the preparation method thereof is as follows: Step 1: Weigh phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand, modified regenerated gravel, water, admixture, carbon fixer, GU release agent, etc. according to the mass ratio of each component; Step 2: Add the phosphorus slag, industrial solid waste composite powder, ordinary Portland cement, modified regenerated sand and modified regenerated gravel weighed in step 1 according to the mass ratio of each component into a mixer and stir for 10 to 15 seconds to mix the powders and aggregates evenly; Step 3: Add the water and admixture weighed in the mass ratio of each component in step 1 to the mixture stirred evenly in step 2, and continue stirring in the mixer for 240-300 seconds. At this time, apply GU release agent evenly on the inner wall of the formwork, and pour it into the mold after the concrete mixing is completed.

Citation Information

Patent Citations

  • High-performance recycled concrete and preparation process thereof

    CN110540389A

  • High-performance concrete with C80 strength grade, and preparation method of high-performance concrete

    CN112142405A

  • High polymer environment-friendly recycled concrete and preparation method thereof

    CN113651579A

  • Modified recycled bare concrete and preparation method thereof

    CN115745514A

  • Self-repairing recycled concrete and preparation method thereof

    CN116514481A